Micropropagation of Pistachio: The Wave of the Future? - Onay, A.; Suzerer, V.; Yildirim, H.; Tilkat, E.; Akdemir, H.; Ozden-Tokatli, Y. (Int Soc Horticultural Science, 2011)
The aim of this review is concerned with the novel in vitro methods published for micropropagation and conservation of pistachio. Since the first publication by Barghchi in 1982, there have been considerable biotechnological advances in both micropropagation and conservation of pistachio germplasm. All of those studies revealed that the success of biotechnological approaches is dependent on regeneration of mature pistachio trees following successful culture initiation, generally by micropropagation. This review is focused upon the novel in vitro methods published for micropropagation and conservation of pistachio in which contributions of Barghchi, Abousalim, Onay, Parfitt, Tilkat and Ozden-Tokatli and others are discussed in a historical perspective. Examples of all aspects of micropropagation (shoot tip culture, somatic embryogenesis and adventive organogenesis) and currently employed uses of pistachio tissue culture, especially practical applications of micropropagation, which enable the pistachio industry to transition into an evaluation of what lies ahead, are also presented. Our work of over 20 years of experience will be presented in relation to past accomplishments, while presenting newer technologies and developments that may provide researchers with knowledge allowing them to determine the practicality and economic validity for micropropagation to become the wave of the future for large-scale commercial propagation of pistachios.
5th International Symposium on Pistachios and Almonds -- OCT 06-10, 2009 -- Univ Harran, Sanliurfa, TURKEY
Keywords: micropropagation; regeneration; plant growth regulators; pistachio; germplasm conservation